Recognition of depressive symptoms by physicians - Sergio Gonçalves Henriques; Renério Fráguas; Dan V. Iosifescu; Paulo Rossi Menezes; Mara Cristina Souza de Lucia; Wagner Farid Gattaz; Milton Arruda Martins (Clinics, 2009)
OBJECTIVE: To investigate the recognition of depressive symptoms of major depressive disorder (MDD) by general practitioners. INTRODUCTION: MDD is underdiagnosed in medical settings, possibly because of difficulties in the recognition of specific depressive symptoms. METHODS: A cross-sectional study of 316 outpatients at their first visit to a teaching general hospital. We evaluated the performance of 19 general practitioners using Primary Care Evaluation of Mental Disorders (PRIME-MD) to detect depressive symptoms and compared them to 11 psychiatrists using Structured Clinical Interview Axis I Disorders, Patient Version (SCID I/P). We measured likelihood ratios, sensitivity, specificity, and false positive and false negative frequencies. RESULTS: The lowest positive likelihood ratios were for psychomotor agitation/retardation (1.6) and fatigue (1.7), mostly because of a high rate of false positive results. The highest positive likelihood ratio was found for thoughts of suicide (8.5). The lowest sensitivity, 61.8%, was found for impaired concentration. The sensitivity for worthlessness or guilt in patients with medical illness was 67.2% (95% CI, 57.4-76.9%), which is significantly lower than that found in patients without medical illness, 91.3% (95% CI, 83.2-99.4%). DISCUSSION: Less adequately identified depressive symptoms were both psychological and somatic in nature. The presence of a medical illness may decrease the sensitivity of recognizing specific depressive symptoms. CONCLUSIONS: Programs for training physicians in the use of diagnostic tools should consider their performance in recognizing specific depressive symptoms. Such procedures could allow for the development of specific training to aid in the detection of the most misrecognized depressive symptoms.